Comparative Analysis of The Use of Nanosilica and Potassium Chloride as Shale Inhibitor in Water Based Mud - Suhascaryo, Nur; Ramadhanti, Syifa Khasyikirana; Ketut Rama Wijaya; Miftahul Jannah (Scientific Contributions Oil and Gas, 2025)
Swelling shale is one of the most common problems encountered in oil and gas drilling operations. Potassium chloride (KCl) is widely applied as a shale inhibitor due to its ionic inhibition mechanism; however, excessive KCl concentrations can have detrimental effects on drilling mud performance. This study examines the potential of nanosilica derived from geothermal industrial waste as a substitute for KCl. Five mud samples were tested: base fluid, 1% nanosilica, 3% nanosilica, 1% KCl, and 3% KCl. The samples were evaluated through a series of physical property tests, including density, rheology, filtration loss, pH, methylene blue test (MBT), K⁺ concentration, and Cl⁻ concentration. Swelling-related parameters were also assessed using Linear Swelling Meter (LSM), accretion tests, and erosion tests under both before hot rolling (BHR) and after hot rolling (AHR) conditions at 200°F for 16 hours. The results indicate that nanosilica improved rheological properties and reduced shale swelling compared to the base fluid. Meanwhile, the 1% KCl formulation demonstrated strong performance in LSM and erosion tests. Overall, nanosilica shows potential as a partial substitute for KCl as a shale inhibitor; however, surface modification and field-scale validation are recommended for further confirmation.